Breeding population of the Rook "Corvus frugilegus" in the Świętokrzyskie Mountains - current state and trends - Chmielewski, Sławomir; Iwańczuk, Cezary; Kuropieska, Rafał; Łukaszewicz, Marcin; Szafrański, Adrian; Tabor, Jacek; Tęcza, Robert (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In 2017-2019, a nesting survey of the Rook "Corvus frugilegus" was carried out in the Świętokrzyskie Mountains (14,400 km2). The majority of controls were con?ducted in April. Overall, 15,622 nests were recorded at 166 sites. Mean density was 108.5 nests/100 km2 and 1.2 colonies/100 km2. Rooks most often nested in large colo?nies (101 to 500 nests), comprising 61.5% of all nests and 27.1% of all colonies. Most colonies were located on deciduous trees (77.1%), in contrast to the low number on coniferous trees (4.8%).
Keywords: Rook Corvus frugilegus; Świętokrzyskie Mountains; population size; population density; number and density; habitat preferences